HUBUNGAN PEMBELAJARAN KOOPERATIF PADA BIDANG STUDI PENDIDIKAN AGAMA ISLAM DENGAN PRESTASI DI STIS DAYAH AMAL - Fathimah Fathimah (AL-ILMU, 2022)
The purpose of this study is to clarify how collaborative learning relates to using the CIRC model in Islamic religious education. Because the teacher-centric course process is still the result of problem identification in this study, this study shows the impact on learning outcomes when using the Case Cooperative Integrated Reading and Composition (CIRC) subject model. This type of survey is a qualitative descriptive survey. Then by determining the desired sample, objective tests (pre-test and post-test) were used with a population of 273 and 30 samples to measure student learning outcomes. Techniques for validating data on sources, adequacy of evaluation, and participation in surveys. The results of this study indicate that the application of the CIRC model for collaborative subjects is effective and has a positive impact on student achievement, such as group collaboration, activities, reactions in discussions, writing notes, and expressing opinions in discussions. In addition, it also improves students' attitudes towards religious values. Keywords: Cooperative Subjects, Cooperative Integrated Reading and Composition, Learning Outcomes.